On the Unique Solvability of a Nonautonomous Functional Differential Equation of Neutral Type - Khusanov, D. Kh. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We present conditions for the existence and uniqueness of solutions of functional differential equations of the neutral type and their continuous dependence on the initial data.